Geothermal Lithology Identification in Air Putih, Lebong, Bengkulu Using Magnetotelluric (MT) Method - Sholeha, Della Zakia; Farid, Muchammad; Refrizon, Refrizon (Department of Physics Education, Universitas Mataram, 2025)
Lebong is one of the areas located in Bengkulu Province and is passed by the Ketaun Segment fault. The fault causes several locations in Lebong to have manifestations such as hot springs, solfatara, and fumarole. This research aims to identify rock lithology with 2D modeling using the magnetotelluric method. The data acquisition process was carried out using a magnetotelluric device with a low frequency of 128 Hz, a medium frequency of 1024 Hz, and a high frequency of 4096 Hz. The sensor in the recording consists of two sensors, namely electric and magnetic. Based on the field survey, the results obtained are several distributions of resistivity values from low, medium, and high. The acquired data was processed using ZONDMT software to obtain 2D modeling. The results of data processing interpret the resistivity value to depth. There are 8 measuring points in one track with a west-southeast direction. Variations in measured resistivity consist of low, medium, and high resistivity. The distribution of low resistivity values (10-25 Ωm) in this area is identified as the response of the caprock, having a depth of <1.5 km, shown in light blue. The distribution of medium resistivity values (40-150 Ωm) shown in green to yellow is identified as a reservoir zone with a depth of >1.8 km. Rocks with high resistivity values (>300 Ωm) shown in red are identified as hot rock zones. Hot rocks are at a depth of 4-6 km. The range of frequency values on the 2D modeling color scale ranges from 1-800 Ωm. The results of this study can be used as a basis for feasibility studies for local governments to develop geothermal energy projects. By knowing the subsurface characteristics, the potential for geothermal energy reserves in Lebong can be evaluated more accurately.